Determining the time-variable part of the toroidal geomagnetic field in the core-mantle boundary zone - Hagedoorn, J.M.; Greiner-Mai, H.; Ballani, L. (Physics of the earth and planetary interiors, 2010)
For the computation of the electromagnetic (EM) core-mantle coupling torque, the geomagnetic field must be known at the core-mantle boundary (CMB). It can be divided into linearly independent poloidal and toroidal parts. As shown by previous investigations, the toroidal field produces more than 90% of the EM torque. It can be obtained by solving the associated (toroidal) induction equation for the electrically conducting part of the mantle, i.e. an initial boundary value problem (IBVP). The IBVP differs basically from that for the poloidal field by the boundary values at the interface between lower conducting and upper insulating parts of the mantle: the toroidal field vanishes, the poloidal field continues harmonically as potential field towards the Earth surface. The two major subjects are to find a suitable algorithm to solve the IBVP and to compute the toroidal geomagnetic field at the CMB. Compared to the poloidal field, the toroidal field at the CMB cannot be inferred from geomagnetic observations at the Earth’s surface. In this study, it is inferred from the velocity field of the fluid core flow and the poloidal field at the CMB using an approximation which is consistent with the frozen-field approximation of the geomagnetic secular variation. This investigation differs from earlier ones by: (i) inferring the poloidal field at the CMB from the observed geomagnetic field using a rigorous inversion of the associated (poloidal) induction equation on which the fluid-flow inversion is based to determine consistently the surface flow velocities at the CMB, (ii) applying orthonormal spherical harmonic functions for the representation of the fields and torques, (iii) solving the IBVP numerically by a modified Crank-Nicolson algorithm, which (iv) allows us to highlight the influence of this approach on the resulting EM coupling torques. In addition to an outline of the derivations of the theoretical formalism and numerical methods, the time-variable toroidal field at the CMB is presented for different conductivity models.